Penggunaan Media Pembelajaran Visual Untuk Meningkatkan Keterampilan Membaca Dan Pelafalan Kosa Kata di Komunitas Manggrove Leaf – Kota Kupang - Elisna Huan; Fransiskus Bustan; Novriani R. Manafe; Gracia M. N. Otta (Fakultas Teknik Universitas Cenderawasih, 2023)
Numerous efforts have been made to improve English language learning in non-formal institutions. One of them is by developing interesting teaching-learning media. The learning media used in this program is a student final exam product which is assessed in the Intensive Reading Course, where students are asked to read continuously about one short story, then conduct it into literary elements such as characterization, storyline, etc. After this progress, creative visual learning media was created using materials like paper or cardboard equipped with attractive colors. The objectives of this program include several things; firstly, improving the English language skills of children in the Manggrove Leaf Community, secondly, through learning media, it can be integrated into mastering vocabulary and pronunciation, and thirdly, children can retell what they hear in their own words. It is hoped that the method applied will continue to increase children's efforts in creative and enjoyable learning processes in various non-formal institutions. Some things that are considered priority problems that must be resolved include first, increasing English vocabulary, second, pronunciation of English vocabulary, and third, increasing enthusiasm and motivation for learning English. The solution offered is creative and fun English learning through visual learning media.